Transition into Veganism: Drivers of Vegan Diet Consumption - Tobias-Mamina, Rejoice Jealous; Maziriri, Eugine Tafadzwa (International Review of Management and Marketing, 2021)
compounds used to boost crop productivity have stimulated consumer and marketer interest in organic food. Organic ingredients are generally viewed as more nutritious, cheaper, cleaner and more environmentally sustainable. Society is currently witnessing a revolution in food intake and habits as people grow more health-conscious. Plant-based diets (vegan diet) are expected to become the next organic food for healthy living. The purpose of the study is to understand the impact of personal factors (health consciousness, subjective norms and perceived value) and product attributes on attitudes towards veganism and vegan diet consumption. The data for this research were collected from 377 students within the Generation Y cohort at an institution of higher learning within the Johannesburg metropolitan area in South Africa. A descriptive and exploratory analysis using quantitative techniques was performed using structured questionnaires. A structural equation modelling (SEM) procedure was applied to achieve the hypotheses testing using the AMOS (version 25.0) package. The findings demonstrated the role of motivational and marketing influences in shaping customer consumption patterns. Social influence, health consciousness, perceived value, product attributes, and attitudes towards veganism positively influence vegan food consumption among millennia in South Africa. The results suggest that the attitude towards veganism depends on both personal and social values. Motivations to preserve the environment and reverence for life forms seem to be mainly driven by personal values. Keywords: veganism, social influence, consumption JEL Classifications: M3, M30, M31 DOI: https://doi.org/10.32479/irmm.11519